(b+45)+(2b-90)+b+90=540

Simple and best practice solution for (b+45)+(2b-90)+b+90=540 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (b+45)+(2b-90)+b+90=540 equation:


Simplifying
(b + 45) + (2b + -90) + b + 90 = 540

Reorder the terms:
(45 + b) + (2b + -90) + b + 90 = 540

Remove parenthesis around (45 + b)
45 + b + (2b + -90) + b + 90 = 540

Reorder the terms:
45 + b + (-90 + 2b) + b + 90 = 540

Remove parenthesis around (-90 + 2b)
45 + b + -90 + 2b + b + 90 = 540

Reorder the terms:
45 + -90 + 90 + b + 2b + b = 540

Combine like terms: 45 + -90 = -45
-45 + 90 + b + 2b + b = 540

Combine like terms: -45 + 90 = 45
45 + b + 2b + b = 540

Combine like terms: b + 2b = 3b
45 + 3b + b = 540

Combine like terms: 3b + b = 4b
45 + 4b = 540

Solving
45 + 4b = 540

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-45' to each side of the equation.
45 + -45 + 4b = 540 + -45

Combine like terms: 45 + -45 = 0
0 + 4b = 540 + -45
4b = 540 + -45

Combine like terms: 540 + -45 = 495
4b = 495

Divide each side by '4'.
b = 123.75

Simplifying
b = 123.75

 

See similar equations:

| 0.25(28x-8)=7x-2 | | 2x+3=9x-11 | | 6x+30=-36 | | c=-3+0.1y | | 2x^2+5x+12=0 | | -13=9+2n | | 9y=8y-3 | | 4(x+2)=-3(-2x-4)+x | | 103+x=93+x | | 12z+2y+3z-y= | | -180x^2+21x^3+3x^4=0 | | 2d+18=2d+18 | | 3x-37=x+91 | | 5(3x+10)-2(2x+9)=4-9(3x+2) | | 4ln(3x+4)=10 | | 15v-40=26-8v | | 7n+8(1+7n)=-3n+8 | | -7n+8n= | | 2x-23=x+33 | | 0.60x+.60(50)=0.30(36) | | -172=2x+6(-x+22) | | 2(x-16)=44 | | y-46=278 | | -27+21p=6p-6+15p | | x+13=2x-23 | | 3x+17=9(x-1)+8 | | 8-(4-x)=5+x | | 4(x-1)-5=3x+7 | | 8n+10n= | | 3z^2-2z-33= | | 8c^2-18cd-5d^2= | | 20y+1=71 | | 2p+4p= | | 2(4q-12)+39=6q+1 | | 8w-5= | | -2p+4p= | | 45x^4+15x^6=0 | | 8-5(2-5x)-3(2x-3)=9+14x | | (4x+4)(5x+7)=0 | | 7r+7+1r= | | x^2+16=1 | | (3z^2-2z-33)= | | 5.44=0.34a | | 12(.25-1)=12 | | 3a-1=14-2a | | 3(1-2b)+5(7b-8)=50 | | 7x^2+7x-6=0 | | n-10+8n+3= | | 6y+2=3(3+2y) | | 15=-2(2T+1) | | x/5+7=18 | | 2x-(5x+5)=3x-17 | | 8-4(2-5x)-3(2x-3)=9+14x | | 17p+10+52q+13p-2q= | | 4y+2=6(8y-7) | | 49b^3-4b=0 | | 10x-15=0 | | 36x+2=0 | | 4x+7+x=3(x-1) | | 14=10+2n | | 2x^2=182 | | -(12-4x)+8(10-x)=x | | 4(5-2x)+6+2x= | | 5x+12=6+3x | | 3(2c-5)-4(2-c)=3(4c-5) |